ENHANCING THE POWER OF VOLUNTEER NETWORKS TO IMPROVE THE QUALITY OF LIFE IN THE BUDDHIST WAY FOR THE ELDERLY IN KRATHUM BAEN DISTRICT, SAMUT SAKHON PROVINCE - Thanawongso, Phrakhru Palad Somsak (Journal of Liberal Art of Rajamangala University of Technology Suvarnabhumi, 2025)
This study utilized a participatory action research approach to explore concepts for improving the quality of life in the Buddhist way for the elderly and empowering volunteer networks to improve their quality of life. The research was carried out in Krathum Baen District, Samut Sakhon Province. Data were collected through interviews and workshops with 20 key informants. Content analysis was conducted using triangulation techniques. The findings revealed three points. First, improving the quality of life for the elderly in the Buddhist way could be achieved by developing a manual on improving quality of life in terms of health promotion, aging deceleration, and extension of life, to include using the Buddhist way for volunteers to reflect the relationship between training and quality of life changes through learning activities involving the participation of volunteer networks. This resulted in inspiration and the creation of knowledge covering multiple dimensions, including health, religious activities, technology, and communication with the elderly. Second, empowering volunteer networks to improve the quality of life for the elderly in the Buddhist way could be achieved by volunteer leaders participating in training activities, transforming the roles of trainees from recipients of knowledge to practitioners. Last, the model for empowering volunteer networks to improve the quality of life for the elderly in the Buddhist way was designed to care for and develop the quality of life for the elderly. The results included better overall health for the elderly, increased communication and more time together in families and communities, increased adaptability and confidence in using technology, and a stronger volunteer network, serving as a long-term support base for the elderly. Additionally, the creation of occupational groups should provide additional income, resulting in cooperation in systematic care for the elderly.